Does #selling sell? Analyzing content of CryptoKitties traders’ talk on Discord - Serada, Alesha (CEUR-WS, 2023)
Blockchain technologies have further gamified finances and created new classes of tradeable digital assets. Their early adopters anticipate mutually beneficial ‘sharing economy’ on integrated blockchain platforms, but the practice of non-fungible token (NFT) trading seems to be undermined by the dubious ‘ludic ethics’ of virtual worlds. To find out who benefits from decentralized ecologies on blockchain, this study explores the marketplace of the first popular and the longest-running blockchain-based game CryptoKitties. It uses mixed methods content analysis to analyze textual communication on the gaming platform Discord that serves as the primary tool to advertise tokens on sale. Quantitative measurements and qualitative assessment are applied to approximately 100,000 lines of marketing messages posted in the dedicated channel within the first two years of the game's existence, which encompasses development, maturation and decline of the CryptoKitties market. Three main ways of value construction in NFTs emerge from the linguistic data based on three main types of actors: developers, players, and traders. Furthermore, four distinct clusters of sellers are revealed, whose marketing strategies are characterized by both qualitative and quantitative differences in the language. According to the data, the gaming ecology of CryptoKitties relies on informational asymmetry and monopolization of buyers’ attention. This suggests that a typical NFT marketplace could be better described as a ‘bazaar economy’, rather than a ‘sharing economy’.
Keywords: Non-fungible tokens; multiplayer games; virtual economies; Discord; mixed method content analysis; fi=Viestintätieteet|en=Communication Studies|